Identification of Genes in Diagnosing Major Depressive Disorder with Anorexia Through Bioinformatics Analysis - Guo F; Li Y; Cheng J; Wang X; Hu W; Zhang K; Jing X; Xing J; Liu Z; Zhang H; Liu P (Neuropsychiatric Disease and Treatment, 2025)
Fengtao Guo,1,2 Ying Li,2,3 Junxiang Cheng,1,2 Xinxia Wang,1,2 Wei Hu,1,2 Kun Zhang,4 Xushu Jing,1,2 Jinrui Xing,1,2 Zhifen Liu,1 Huanhu Zhang,2,5 Penghong Liu1,2 1Department of Psychiatry, First Hospital of Shanxi Medical University, Taiyuan, Shanxi, People’s Republic of China; 2Shanxi Medical University, Taiyuan, Shanxi, People’s Republic of China; 3School of Basic Medical Sciences, Shanxi Medical University, Taiyuan, Shanxi, People’s Republic of China; 4Shanxi Mental Health Center, Taiyuan Fifth People’s Hospital, Taiyuan, Shanxi, People’s Republic of China; 5Shanxi University of Chinese Medicine, Jinzhong, Shanxi, People’s Republic of ChinaCorrespondence: Huanhu Zhang, Shanxi Medical University, Taiyuan, SX030001, People’s Republic of China, Tel +86-13593166631, Email zhhh31@163.com Penghong Liu, Department of Psychiatry, First Hospital of Shanxi Medical University, Taiyuan, SX030001, People’s Republic of China, Tel +86-18634363075, Email liupenghong6@163.comBackground: Researches have indicated that major depressive disorder (MDD) and anorexia may have overlapping pathogenic mechanisms. In light of this, we endeavored to identify diagnostic gene candidates for MDD in individuals with comorbid anorexia.Methods: Gene expression data pertaining to MDD and healthy controls (HC) were retrieved from the Gene Expression Omnibus (GEO) database. Utilizing Limma and weighted gene co-expression network analysis (WGCNA), key MDD-associated genes were meticulously screened. Subsequently, these genes were cross-referenced with established anorexia-related genes to pinpoint common genetic factors shared between MDD and anorexia. Further refinement was conducted using Cytoscape software to identify hub-genes. Ultimately, animal experiments were conducted to validate and confirm the findings.Results: We identified a total of 214 genes that are commonly associated with both MDD and anorexia. These genes were found to be enriched in inflammatory and immune-related pathways. Among these 214 genes, six were distinguished as hub-genes: IL10, ITGAM, PTPRC, IL13, STAT5B, and JAK2. Immune infiltration analysis further revealed that all these hub-genes exhibited associations with multiple immune cell types. Animal experiments demonstrated that, compared to control mice, the model group exhibited significantly elevated expression levels of PTPRC, STAT5B, and JAK2.Conclusion: Through the application of bioinformatics analysis and animal experimentation, we have pinpointed three hub-genes (PTPRC, STAT5B, and JAK2) that hold potential as both diagnostic biomarkers and therapeutic targets for MDD accompanied with anorexia.Keywords: major depressive disorder, anorexia, inflammation, bioinformatics analysis, differentially expressed genes